Extensive Extragenital Lichen Sclerosus-Like Lesions in a Patient with Junctional Epidermolysis Bullosa - Smriti Gupta; Sanjeev Handa; Debajyoti Chatterjee; Dipankar De; Rahul Mahajan (Wolters Kluwer Medknow Publications, 2024)
Epidermolysis bullosa (EB) is a heterogeneous group of genetic disorders characterized by the formation of blisters either spontaneously or at the sites of trauma. These heal with post-inflammatory hypopigmentation, scarring, or milia formation. We hereby present a child who presented with widespread hypopigmented atrophic areas, blistering at trauma-prone sites, and nail dystrophy. The significance of this particular case lies in the challenge of distinguishing between epidermolysis bullosa and bullous extragenital lichen sclerosus et atrophicus.